Pengaruh Profitabilitas (ROE), Ukuran Perusahaan, Financial Distress, Dan Opini Audit Terhadap Auditor Switching Pada Perusahaan Manufaktur Di BEI Tahun 2017-2019 - Annisa Nauli Sinaga; Mega Mega; Felline Felline; Osvaldo Romi Wijaya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to examine and examine the effect of profitability with indicators of ROE, company size, financial distress and audit opinion on auditor switching in manufacturing companies on the IDX in 2017-2019. This research uses descriptive quantitative methods, using secondary data and documentation study collection techniques. Manufacturing companies have a population of 166 where there are only 122 companies that can be sampled. Data analysis used logistic regression. The test results show that simultaneously profitability, company size, financial distress and audit opinion have an effect on auditor switching in manufacturing companies on the IDX in 2017-2019 while individually only audit opinions have an influence on auditor switching. Keywords : Profitability (ROE), Company Size, Financial Distress, Audit Opinions and Auditor Switching.